Dysregulated tRNA-derived fragments impair fatty acid metabolism in intrahepatic cholestasis of pregnancy - Lian Yang; Xia Yu; Shimao Zhang; Jinzhu Fu; Mengjun Luo; Wei Shen; Cheng Huang; Xiao Yang; Xiao Yang (Frontiers in Medicine, 2025)
ObjectiveIntrahepatic cholestasis of pregnancy (ICP) is a common obstetric complication that occurs predominantly in the mid-to-late gestational period, but its exact etiology remains unclear. Recent studies have revealed that transfer RNA-derived fragments (tRFs) are closely associated with various diseases; however, whether tRFs contribute to ICP pathogenesis remains unknown. This study was designed with the objectives of investigating the expression profiles of tRFs in patients with ICP, exploring the potential correlation between tRF expression and maternal–fetal pathophysiological changes, identifying novel early diagnostic biomarkers, and ultimately enhancing clinical management strategies.MethodsSerum samples were collected from 3 ICP patients and 3 healthy controls before delivery. Small RNA sequencing was performed via the Illumina platform, and the obtained sequences were aligned and screened against the tRFdb database to identify differentially expressed tRFs. Potential target genes of tRFs were predicted, followed by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses to assess their functional implications.ResultsCompared with controls, ICP patients presented significant differential expression of 5 tRFs, including 2 upregulated tRFs and 3 downregulated tRFs, in prenatal serum. Furthermore, GO and KEGG analyses suggested that fatty acid degradation might be associated with 3003a_trf-3 and 3005b_trf-3.ConclusionThis study provides preliminary data for the validation of serum-based biomarkers in ICP patients. The findings suggest that tRF dysregulation may be involved in ICP pathogenesis via the fatty acid degradation pathway, offering new molecular insights and a foundation for the development of early intervention strategies to prevent adverse fetal outcomes. These conclusions require further validation in larger sample cohorts.